PENGARUH BUFFER SIZE PADA SISTEM MANET DENGAN MENGGUNAKAN METODE SCHEDULING FIFO - Andriyanto, Enrico; Diafari Djuni H, I.G.A.K; Wirastuti, N.M.A.E.D. (Jurnal SPEKTRUM; Vol 6 No 2 (2019): Jurnal SPEKTRUM, 2019)
MANET or Mobile Ad Hoc Network is a technology in Ad Hoc network that is mobile and its own use is very wide because, nodes-nodes in this network is moving randomly so that the network topology is also always changing. Setting Buffer size with Scheduling method using FIFO can improve the quality of this network. This simulation uses OPNET Modeler 14.5 by comparing the effect of the Buffer Size value change. Buffer Size parameter values will be changed to 20000 bits, 30000 bits, and 40000 bits using 20 nodes. QoS of MANET performance is a method of measuring how good a network is and an attempt to define the characteristics and properties of a service. The results of this study can be seen the value of delay, packet loss and throughput have obtained the appropriate results and already meet ITU standards with the lowest delay value of 1.30 millisecond and the value of throughput with 258,096 bps.